2006
DOI: 10.1149/1.2356353
|View full text |Cite
|
Sign up to set email alerts
|

Green Laser Crystallization of a-Si Films Using Preformed a-Si Lines

Abstract: In this work, amorphous silicon films with preformed a-Si lines were crystallized using a diode pumped solid state green laser irradiating at 532 nm. The possibility of controllable formation of grain boundaries was investigated. The crystallization processes in the rapidly melted silicon films were discussed. The influence of the crystallization parameters (i.e., energy density, scan velocity, etc.) and structure type (i.e., with and without preformed lines) on properties of the crystallized films was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…CMOS post-processing and 3D device integration (1)(2)(3)(4). We recently demonstrated TFTs with competitive mobility values, good ring oscillator performance and low off-state currents (6). This competitive TFT performance was among others enabled by the high-quality plasma-deposited SiO 2 , which could be realized having sufficient understanding of the impact of plasma-deposition conditions on film (electrical) properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMOS post-processing and 3D device integration (1)(2)(3)(4). We recently demonstrated TFTs with competitive mobility values, good ring oscillator performance and low off-state currents (6). This competitive TFT performance was among others enabled by the high-quality plasma-deposited SiO 2 , which could be realized having sufficient understanding of the impact of plasma-deposition conditions on film (electrical) properties.…”
Section: Introductionmentioning
confidence: 99%
“…A very low midgap interface state density of 3⋅10 10 eV -1 ⋅cm -2 was obtained. These films were successfully applied in the fabrication of low-temperature TFTs with a competitive performance (6,9). The purpose of this work is to demonstrate that modeling of gas-phase reactions can contribute significantly to understand properties of films deposited at different deposition conditions.…”
Section: Introductionmentioning
confidence: 99%
“…CMOS post-processing and 3D device integration. We recently demonstrated that our ICPECVD gate oxides [1], applied to low-temperature TFTs, exhibited competitive mobility values, good ring oscillator performance and low off-state-currents [2]. The competitive TFT performance was among others enabled by the high-quality plasma-deposited SiO 2 , which could be realized having sufficient understanding of the impact of plasma-deposition conditions on film (electrical) properties.…”
mentioning
confidence: 99%
“…The average energy density in the beam was adjusted by an optical attenuator. The energy density was defined as the total pulse energy divided by the Full-Width Half-Maximum (FWHM) area of the beam [30][31][32].…”
Section: Laser Crystallization Equipmentmentioning
confidence: 99%
“…Following the sequential lateral solidification approaches using spacers and seeds, we recently proposed a new approach to control the location of grain boundaries [30][31][32], as illustrated in Figure 6.3. An amorphous silicon layer (with typical thickness 50-100 nm common for poly-Si TFTs [130]) is deposited over parallel amorphous silicon lines, oriented in the lasercrystallization direction.…”
Section: Grain Boundary Location Control Approachmentioning
confidence: 99%